Moving Forward : Connectivity and Logistics to Sustain Bangladesh’s Success - Herrera Dappe, Matías; Kunaka, Charles; Lebrand, Mathilde; Weisskopf, Nora (Washington, DC: World Bank, 2019)
The erosion of its competitiveness is raising concerns about the sustainability of Bangladesh's growth model based on exports of ready-made garments. To safeguard its comparative advantage in ready-made garments and diversify its exports basket, Bangladesh needs to increase its competitiveness. Improving logistics performance is an important lever with which to do so.